Faktor – Faktor Pergeseran Fungsi Rumah Hunian di Kampung Batik Kauman, Kota Pekalongan - Iin Isnaeni; Diah Intan Kusumo Dewi (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Kauman, where located in downtown Pekalongan is one of the batik clusters in Pekalongan City. Since 2007, Kampung Kauman was established to be one of batik tourism village in Pekalongan city. Location dan development in Kampung Batik kauman as batik village has an impact on the physical development in Kampung Batik Kauman, one of which is marked by the transformation function of residental house into a business house. Based on the phenomenon, this study aims to analyze factors that affected housing function transformation in Kampung Batik Kauman. The approach used in his research is a descriptive quantitative method. From the research result can be seen that there are five types of business houses in Kampung Batik Kauman: residential house and batik production; residential houses and batik showroom; residential house, production and batik showroom; residential house and boarding house; and residential, trading and service house (expect batik). Internal factors that affected the community in making housing function transformation in Kampung Batik Kauman is a factor employment and income level. External factor that affected the community in making housing function tranformation id a development of the surrounding area in Kampung Batik Kauman.